“I felt like I was providing half a service”: Challenges, solutions, and action items for paramedicine when encountering patients experiencing intimate partner violence - Rory A. Marshall; Tori N. Stranges; Nicole Merritt; Stephen Bartlett; Simon Sawyer; Paul van Donkelaar (PLoS ONE, 2026)
Introduction Intimate partner violence (IPV) is a pervasive and damaging global crisis. In response to the harmful health consequences, survivors often attempt to access the healthcare system. Paramedics are often the first point of contact with the healthcare system. Objective: Examine how the perspectives and experiences of paramedics may inform our understanding of current clinical practice and guide potential improvements for paramedicine. Methods An interpretive description qualitative approach was used to design and conduct this research. Paramedics participated in focus groups discussing the intersection of paramedicine and IPV from the practitioner perspective. De-identified focus group transcripts underwent inductive pattern recognition. From the patterns, common challenges were identified. Corresponding solutions and action items were identified. Results N = 17 paramedics (Women n = 7 (41%), Men n = 10 (59%); Mean Age 34 ± 10 years) participated in four focus groups. Even without clinical practice guidance for IPV, participants shared the service they were providing did not meet the needs of survivors. Common challenges at the intersection of paramedicine and IPV were: 1) patient barriers for help seeking, 2) individual paramedic disposition, 3) individual paramedic confidence, 4) paramedic service education, training, and readiness, 5) paramedic service guidance, 6) paramedic service configuration, and 7) interagency networks. Solutions and action items to address each challenge included updating functional education, training, infrastructure, and policy. Conclusion Participants indicated that substantial challenges exist from the paramedic perspective at the intersection of paramedicine and IPV. Solutions and action items to bolster the education, training, infrastructure, policy, and positioning of paramedics were identified, providing positive direction. Meaningful, evidence-based implementation of these results should be pursued to advance the profession. Paramedics can be positioned as expert resources for survivors of IPV, linking through to vital supports that promote positive outcomes.